The current paradigm of the EU energy system and its impact on the sustainability of member states’ economies by 2050 - Zhao, Long; Manta, Otilia; Militaru, Iuliana; Folcut, Ovidiu (Frontiers in Environmental Science, 2022)
In a context of multi-crises, as well as the challenges of both the medium and long term, associ-ated with elements highlighted by the transformation of the EU energy system, we appreciate that not only is it a very difficult time to overcome efficiently and balanced EU Member States, but above all it is a time to activate research systems on identifying key solutions, as well as firm de-cisions at the level of decision-making institutions at the level of the European Commission. Moreover, based on the latest European studies, systematic testing of ongoing initiatives can strategically prepare for an increase in the resilience of Member States' economies to crisis shocks, as well as "the key to success Europe’s ecological transformation and climate neutrality of the EU economy in a broader sense”. The paper aims to highlight how to act at European level in the context of the latest energy decisions (regulations, strategies, programs and directives) and how to stimulate "the EU economy with about 3.3% of EU GDP or EUR 464 billion in 2030 and up to EUR 5.6% or more than EUR 1 trillion in 2050”. At the same time, we appreciate that as a result of green energy, digitalization and technology, the environmental objective on the EU and UN netzero emissions in 2050 can be achieved, especially as a result of a fair and equitable transfor-mation for the economic environment and for citizens, being an objective that directly contributes to achieving a sustainable, collaborative and prosperous society with an open and modern society, but more chosen efficiently in terms of resource optimization and a sustainable and competitive economy.